Ureterorenoskopie - Gross, Andreas; Rassweiler, Jens; Häcker, Axel (Der Urologe, 2017)
Ureterorenoscopy (URS) is a minimally invasive treatment option for removal of kidney stones, which has gained importance in this field over the past two decades. This technique has replaced extracorporeal shock wave lithotripsy (ESWL) stone surgery for many indications. It is also particularly important in the diagnostics and treatment for tumors of the upper urinary tract. This article describes the indications, surgical technique and management of complications of URS.